First comparative analysis concerning the plasma platelet contamination during MNC collection. Issue 4 (August 2017) - Pfeiffer, Hella; Achenbach, Susanne; Strobel, Julian; Zimmermann, Robert; Eckstein, Reinhold; Strasser, Erwin F.
Abstract: Background and objectives: Monocytes can be cultured into dendritic cells with addition of autologous plasma, which is highly prone to platelet contamination due to the apheresis process. Since platelets affect the maturation process of monocytes into dendritic cells and might even lead to a diminished harvest of dendritic cells, it is very important to reduce the platelet contamination. A new collection device (Spectra Optia) was analyzed, compared to two established devices (COM.TEC, Cobe Spectra) and evaluated regarding the potential generation of source plasma. Materials and methods: Concurrent plasma collected during leukapheresis was analyzed for residual cell contamination in a prospective study with the new Spectra Optia apheresis device ( n = 24) and was compared with COM.TEC and Cobe Spectra data (retrospective analysis, n = 72). Donor pre-donation counts of platelets were analyzed for their predictive value of contaminating PLTs in plasma harvests. Results: The newest apheresis device showed the lowest residual platelet count of the collected concurrent plasma (median 3.50 × 10 9 /l) independent of pre-donation counts. The other two devices and sets had a higher platelet contamination. The contamination of the plasma with leukocytes was very low (only 2.0% were higher than 0.5 × 10 9 /l). Conclusions: This study showed a significant reduction of platelet contamination of the concurrent plasma collected with the new Spectra Optia device. This plasma product with low residual platelets and leukocytes might also be used as plasma for fractionation.